1993
DOI: 10.3109/00365549309008547
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Liberation from Neisseria meningitidis Correlates to their Ability to Induce Procoagulant and Fibrinolytic Factors in Human Monocytes

Abstract: Endotoxin released from different strains of Neisseria meningitidis were studied for their ability to induce procoagulant (tissue factor, TF), fibrinolytic (plasminogen activator, PA) and antifibrinolytic (plasminogen activator inhibitor 2, PAI-2) factors in human monocytes. Two meningococcal strains that liberate endotoxin (E+; 270+ and 840+) and 2 non-liberating (E-; 270- and 840-) strains were used. The endotoxin activity in culture filtrates of these strains was monitored with the Limulus amoebocyte lysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…As a result, they concluded that vesicle-associated LPS is the native presentation of LPS that has the highest biological activity. In a similar comparison, endotoxin secreted into the culture supernatant from N. meningitidis cells was found to more effectively stimulate monocyte expression of plasminogen activator and the procoagulant factor TF than phenol-extracted, pure LPS (119).…”
Section: Lps and Other Pampsmentioning
confidence: 84%
See 1 more Smart Citation
“…As a result, they concluded that vesicle-associated LPS is the native presentation of LPS that has the highest biological activity. In a similar comparison, endotoxin secreted into the culture supernatant from N. meningitidis cells was found to more effectively stimulate monocyte expression of plasminogen activator and the procoagulant factor TF than phenol-extracted, pure LPS (119).…”
Section: Lps and Other Pampsmentioning
confidence: 84%
“…Vesicles from Treponema denticola, a periodontopathogen, have active proteases that confer host cell-damaging characteristics similar to those of the whole bacterium (19,116,119). In addition, Neisseria meningitidis culture supernatant endotoxic filtrates have procoagulant and fibrinolytic factors for human monocytes (119).…”
Section: Nontoxin Virulence Factors In Om Vesiclesmentioning
confidence: 99%
“…Most of our knowledge of sepsis-induced DIC originates from infusion experiments with endotoxin, TNF, or other cytokines such as IL-1 and IL-6 and in vitro experiments with monocytes or endothelial cells exposed to these compounds (287,288,412,486). One of the initial procoagulant processes elicited was the expression of TF, the initial step in the activation of the extrinsic coagulation pathway (218) that ultimately results in thrombin formation.…”
Section: Pathophysiology Of Fulminant Meningococcal Sepsismentioning
confidence: 99%
“…Most of our knowledge of sepsis-induced DIC originates from infusion experiments with endotoxin, TNF, or other cytokines such as IL-1 and IL-6 and in vitro experiments with monocytes or endothelial cells exposed to these compounds (287,288,412,486). One of the initial procoagulant processes elicited was the expression of TF, the initial step in the activation of the extrinsic coagulation pathway (218) that ultimately results in thrombin formation.…”
Section: Pathophysiology Of Fulminant Meningococcal Sepsismentioning
confidence: 99%